2018
DOI: 10.3389/fphys.2018.00301
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Stochastic Vestibular Stimulation to Improve Locomotor Performance During Adaptation to Visuomotor and Somatosensory Distortion

Abstract: Astronauts exposed to microgravity face sensorimotor challenges affecting balance control when readapting to Earth's gravity upon return from spaceflight. Small amounts of electrical noise applied to the vestibular system have been shown to improve balance control during standing and walking under discordant sensory conditions in healthy subjects, likely by enhancing information transfer through the phenomenon of stochastic resonance. The purpose of this study was to test the hypothesis that imperceptible leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 64 publications
1
20
0
1
Order By: Relevance
“…For the sinusoidal-based condition, we set the SVS intensity to 50% of the participant's sinusoidal threshold [21,28]. For the cutaneous-based condition, we set the SVS intensity to 80% of the participant's cutaneous threshold [17,19,20].…”
Section: Stochastic Vestibular Stimulationmentioning
confidence: 99%
See 1 more Smart Citation
“…For the sinusoidal-based condition, we set the SVS intensity to 50% of the participant's sinusoidal threshold [21,28]. For the cutaneous-based condition, we set the SVS intensity to 80% of the participant's cutaneous threshold [17,19,20].…”
Section: Stochastic Vestibular Stimulationmentioning
confidence: 99%
“…In addition, joint range of motion and variability, step width and step-width variability, and metrics of local dynamic stability (quantified by maximum finite-time Lyapunov exponents) differ between these walking conditions [25][26][27]. Although Temple et al [28] recently found that SVS resulted in faster completion time on a mobility course that required overground walking on foam while adapting to a visual perturbation, they did not report the effects of SVS on measures of balance or gait performance. As such, it is unclear whether the improvements in stability reported in Mulavara et al [24] translate to overground walking.…”
Section: Introductionmentioning
confidence: 99%
“…Two recent studies have analyzed the effects of nGVS on gait (Iwasaki et al 2018;Temple et al 2018). Iwasaki et al (2018) investigated the effects of nGVS on walking speed in healthy people and people with BVP.…”
Section: Functional Effects Of Ngvs On Gaitmentioning
confidence: 99%
“…In this Neuro Forum, we discuss six recent articles (Inukai et al 2018a(Inukai et al , 2018bIwasaki et al 2018;Keywan et al 2018;Temple et al 2018;Wuehr et al 2018) that have explored the effects of nGVS on balance and gait in humans. Second, we discuss the potential mechanisms of the observed effects and, based on the current state of the art, give recommendations and directions for future research on nGVS for the purpose of improving balance and gait.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have investigated motor adaptation using a variety of experimental paradigms. One of the ways is by studying the changes in the movement characteristics produced by adding and subsequently removing sensory (visual, proprioceptive, acoustic, and vestibular) distortions or perturbations while performing motor tasks [2][3][4][5]. One of the common locomotor adaptation paradigms involves studying locomotor changes by altering the normal interlimb relationship during walking by changing the speeds of treadmill belts relative to each other (commonly called split-belt treadmill participants were screened using a modified physical activity readiness questionnaire (PAR-Q) [37].…”
Section: Introductionmentioning
confidence: 99%